Global Cerebral Ischemia in Male Long Evans Rats Impairs Dopaminergic/ΔFosB Signalling in the Mesocorticolimbic Pathway Without Altering Delay Discounting Rates - Morin, Alexandre; Poitras, Marilou; Plamondon, Hélène (Frontiers in Behavioral Neuroscience, 2022)
Global cerebral ischemia (GCI) in rats has been shown to promote exploration of anxiogenic zones of the Elevated Plus Maze (EPM) and Open Field Test (OFT). This study investigated changes in impulsive choice and/or defensive responses as possible contributors of heightened anxiogenic exploration observed after ischemia. With these responses being regulated through mesocorticolimbic monoaminergic pathways, we also characterised post-ischemic changes in the expression of dopamine D2 receptors (DRD2), dopamine transporters (DAT), and ΔFosB in the basolateral amygdala (BLA), nucleus accumbens core (NAcC) and shell (NAcS), and ventromedial prefrontal cortex (vmPFC). Impulsivity was assessed using delay discounting (DD) paradigms, while the Predator Odour Test (PO) served to assess changes in defensive responses towards a naturally aversive stimulus. Male Long Evans rats underwent 9 days of autoshaping training and 24 days of DD training prior to GCI or sham surgery (n = 9/group). Post-surgery, rats completed the OFT, EPM, and PO, followed by 6 days of DD sessions. Blood droplets served to evaluate corticosterone secretion associated with PO exposure. Our findings revealed no impact of GCI on delay discounting rates, while PO approach behaviours were minimally affected. Nonetheless, GCI significantly reduced DRD2- and ΔFosB-ir in the NAcS and NAcC, respectively, while DAT-ir was diminished in both NAc subregions. Collectively, our findings refine the understanding of cognitive-behavioural and biochemical responses following stroke or cardiac arrest; they support significant alterations to the dopaminergic mesocorticolimbic pathway after ischemia, which are not associated with altered impulsive choice in a DD task but may influence locomotor exploration of the OFT and EPM.